Legal Reform on the Supervisory Mechanism of Supreme Court Judges in Realizing Accountable Judicial Independence Based on Legal Certainty - Ismu Bahaiduri Febri Kurnia; Zainal Arifin Hoesein (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
This study aims to analyze the legal provisions of the Supreme Court's supervisory mechanism, identify problems that hinder the realization of accountable judicial independence, and formulate legal reforms for the supervision of Supreme Court judges based on legal certainty. The study uses a normative juridical method with a statutory and conceptual approach. The findings of the study suggest that the oversight of Supreme Court judges is governed by the 1945 Constitution of the Republic of Indonesia, the Law on Judicial Power, the Law on the Supreme Court, and the Law on the Judicial Commission. This oversight is implemented through both internal and external supervisory mechanisms. However, various problems remain in the form of overlapping authority between the Supreme Court and the Judicial Commission, unclear boundaries between ethical and technical judicial supervision, weak institutional coordination, and less than optimal effectiveness of follow-up on supervisory results, resulting in legal uncertainty and declining public trust in the judiciary. Legal reforms need to be carried out through regulatory harmonization, affirmation of the division of supervisory authority, strengthening the position of Judicial Commission recommendations, increasing transparency of the supervisory process, and establishing an integrated supervisory system capable of maintaining a balance between the independence and accountability of judges. These reforms are expected to strengthen judicial integrity and ensure legal certainty in the administration of judicial power.